Pembuatan Indeks Beranotasi Jurnal Kedokteran Tahun 2015 Perpustakaan Fakultas Kedokteran Universitas Andalas - Harianti, Siska; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about the creation of an annotated index of medical journals in 2015 in the Library of the Faculty of Medicine, University of Andalas. The purpose of this paper is to describe the process of making an annotated index of journal articles in 2015 in the Library of the Faculty of Medicine, University of Andalas. Data were collected through interviews and observations by direct observation of the original material in the Library of the Faculty of Medicine, University of Andalas. Based on the research results, we can conclude the steps to create an annotated index of medical journals as follows: (1) the collection and selection of journals is done directly in the Library of the Faculty of Medicine, University of Andalas; (2) make a detailed list of the number of articles contained in journals; manufacture of articles are recording a description of each article; (3) creation of annotations article containing a glimpse into the content of articles in the journal which will help pemustaka in tracing the information needed; (5) the determination of keywords; (6) create the index; (7) and typing the index as well as examination of the indices that have been typed to avoid mistakes in typing.Keyword:Â  index, annotation, journals, medical.